The interaction of energy services, breakthrough technologies, and human need satisfaction. EconTrans working paper #1 - Thomas Schinko; Ariane Weifner; Angela Köppl (Austrian Institute of Economic Research (WIFO), 2021)
In the context of research on long-run transformations, such as the low-carbon energy transformation, research interest is growing on how to define and measure human wellbeing meaningfully. The working paper provides a thorough discussion of the literature on well-being and human needs in the context of energy consumption and confronts this scientific discourse with the concept of energy services, or functionalities. Based on a thorough literature review and a comprehensive stakeholder consultation process, we show, that energy services represent the crucial link between energy use (and related GHG emissions) and human need satisfaction.
Keywords: 330